Performance and Fuel Efficiency Evaluation of an Injection Converter Kit Retrofit on a 100cc Four-Stroke Engine - Al-mukharom, Mohammad Rizky; Hadi, Samsul (Universitas Negeri Padang, 2025)
This study investigates the effectiveness of an injection converter kit as a small engine retrofit for improving torque and fuel efficiency in a 100cc four-stroke motorcycle engine. An experimental method was applied using two fuel systems: a conventional carburetor and a retrofit converter kit. Torque and fuel consumption were measured across engine speeds ranging from 3000 to 7000 rpm using a dynamometer and volumetric analysis. The injection system achieved a peak torque of 6.78 N·m at 3600 rpm, exceeding the carburetor’s 5.90 N·m at 5300 rpm. It also demonstrated improved fuel economy at most RPM levels, with a spike at 6000 rpm due to overpressure. Statistical analysis via Two-Way ANOVA confirmed the significance of these differences. The results suggest that the injection converter kit is a viable small engine retrofit option for enhancing performance and efficiency in low-displacement motorcycles.